Implantable multifunctional black phosphorus nanoformulation-deposited biodegradable scaffold for combinational photothermal/ chemotherapy and wound healing. (February 2021) - Xue, Chencheng; Sutrisno, Linawati; Li, Menghuan; Zhu, Wei; Fei, Yang; Liu, Changhuang; Wang, Xuan; Cai, Kaiyong; Hu, Yan; Luo, Zhong
Abstract: Surgery is the mainstream treatment for melanoma, but its clinical implementation suffers from some major drawbacks including residual infiltrating melanoma cells at resection margins and severe tissue injury. In this study, a nanocomposite scaffold is developed for in-situ therapy after melanoma surgery as well as wound healing, which is fabricated by embedding photothermal-capable black phosphorus nanosheets (BPNSs) into bioresorbable Gelatin-PCL (GP) nanofibrous scaffold. GP scaffold is a clinically-tested biomaterial with temperature sensitivity and tissue-healing effect, while the BPNSs are loaded with the anticancer antibiotic of doxorubicin (DOX) and conjugated with NH2 -PEG-FA for tumor-targeted delivery. The GP scaffold could undergo a sol-gel transition upon NIR irritation and release the BPNSs in situ. During this process, most of the BP-based nanoformulations were selectively internalized by the melanoma cells for the cooperative photothermal therapy and heat-triggerable DOX therapy, while some of the loaded DOX was released into the wound tissue to create a tumor-suppressive microenvironment. Moreover, BPNSs could be gradually degraded to phosphates/phosphonates and thus enhance tissue repair by activating the ERK1/2 and PI3K/Akt pathway. Meanwhile, the detached DOX molecules would also enter the wound tissues for continuous melanoma inhibition. Considering the anti-melanoma and wound healing effect of this composite scaffold, it may offer a facile strategy for the wound treatment after melanoma surgery.